PENTINGNYA PENDIDIKAN AKHLAK MENURUT AL-GHAZALI DALAM MEMBENTUK KARAKTER SISWA - Nabila Sarifatul Habibah; Magfiroh Adhelia Putri Jasmine; Intan Fajril Fitriani; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
Abstract : The moral degradation crisis among students in the modern era is increasingly evident through the rise of bullying behavior, the decline of respect toward teachers and parents, and the weakening of social ethics within educational environments. This condition indicates that contemporary education tends to prioritize academic achievement over character building and students’ spiritual development. This study aims to analyze the importance of moral education according to Al-Ghazali in shaping students’ character in the modern era. This research employs a library research method by examining Al-Ghazali’s primary works, especially Ihya’ Ulumuddin and Ayyuhal Walad, along with journals and literature related to character education. The data were analyzed using content analysis and descriptive-philosophical analysis techniques. The findings reveal that Al-Ghazali’s concept of moral education, which is based on tazkiyatun nafs (purification of the soul), habituation (riyadhah), and exemplary conduct, remains highly relevant in addressing today’s moral crisis among students. According to Al-Ghazali, education should not merely emphasize intellectual achievement, but also spiritual formation, self-control, and moral awareness. Therefore, Al-Ghazali’s moral education concept can serve as an important foundation for reconstructing a more humanistic, substantial, and applicable character education system in modern schools. Abstrak : Krisis degradasi moral peserta didik di era modern semakin terlihat melalui meningkatnya perilaku perundungan (bullying), lunturnya sikap hormat kepada guru dan orang tua, serta melemahnya etika sosial di lingkungan pendidikan. Kondisi tersebut menunjukkan bahwa pendidikan saat ini cenderung lebih berorientasi pada pencapaian akademik dibandingkan pembentukan karakter dan spiritualitas peserta didik. Penelitian ini bertujuan untuk menganalisis pentingnya pendidikan akhlak menurut Al-Ghazali dalam membentuk karakter siswa di era modern. Penelitian ini menggunakan metode studi kepustakaan (library research) dengan mengkaji kitab-kitab karya Al-Ghazali, khususnya Ihya’ Ulumuddin dan Ayyuhal Walad, serta berbagai jurnal dan literatur terkait pendidikan karakter. Data dianalisis menggunakan teknik analisis isi (content analysis) dan analisis deskriptif-filosofis. Hasil penelitian menunjukkan bahwa konsep pendidikan akhlak Al-Ghazali yang berlandaskan tazkiyatun nafs (pembersihan jiwa), pembiasaan (riyadhah), dan keteladanan memiliki relevansi yang kuat dalam menjawab krisis moral peserta didik saat ini. Pendidikan menurut Al-Ghazali tidak hanya menekankan aspek intelektual, tetapi juga pembentukan jiwa, pengendalian diri, dan penguatan spiritualitas. Oleh karena itu, pemikiran pendidikan akhlak Al-Ghazali dapat menjadi fondasi penting dalam merekonstruksi pendidikan karakter yang lebih humanis, substantif, dan aplikatif di sekolah modern.